2y+3x+1=0

Simple and best practice solution for 2y+3x+1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y+3x+1=0 equation:


Simplifying
2y + 3x + 1 = 0

Reorder the terms:
1 + 3x + 2y = 0

Solving
1 + 3x + 2y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + 3x + -1 + 2y = 0 + -1

Reorder the terms:
1 + -1 + 3x + 2y = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 3x + 2y = 0 + -1
3x + 2y = 0 + -1

Combine like terms: 0 + -1 = -1
3x + 2y = -1

Add '-2y' to each side of the equation.
3x + 2y + -2y = -1 + -2y

Combine like terms: 2y + -2y = 0
3x + 0 = -1 + -2y
3x = -1 + -2y

Divide each side by '3'.
x = -0.3333333333 + -0.6666666667y

Simplifying
x = -0.3333333333 + -0.6666666667y

See similar equations:

| 9=-r | | 12x^2-6x=45 | | b+8b+1=19 | | 0=16t^2-40t-25 | | 100=(65000)x(1+0.016)100 | | r+r+8=14 | | -4(3(-5)-5)= | | F(x)=(x+5)-6 | | -4+35y-1=21y+18+5 | | (21y^5-5y^4-18y^3)/(3y^4) | | 3x-4x+5x-9x= | | f(x)=x^2-16x+67 | | r+r+8=6 | | =(65000)x(1+0.016)100 | | 6a-1=17 | | (y-3)(y-3)=2y^2+2y-12 | | s(t)=-16t^2+20t+6 | | H(x)=25-y | | 2x-5x+5=10 | | t=240t-16t^2 | | 115+59+135+51=x | | 2x+48=12x+8 | | 2=s-2 | | 55+.25x=45+.35 | | 26x^2-2x=0 | | 12x-18=8x+6 | | 890=5(x+16) | | 3-20x^2=11x | | 10x^2+25x+3=0 | | 2=-1t | | .14x+2520=2400 | | 7q+5q= |

Equations solver categories